Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Infomasi, dan Kearsipan, How It Manages? - Andi Kurniati Karmila (Literatify: Trends in Library Developments, 2020)
Scientific journals are the most read-reference for academics. It is no doubt that many academic libraries owned scientific journals. Some kind of scientific reading is certainly well organized. This descriptive study describes the publishing management of Khizanah al-Hikmah: Journal of Library Science, Information and Archives (KHJIPK). Two that are emphasized in this paper are the process of publishing and journal achievements. The data were obtained through interview with journal editors and from the journal website. The results showed that publishing management was online based using Open Journal System (OJS) software. The year 2017 witnessed KHJIPK achieving National Accreditation as Grade 3. The following year, it lifted to Grade 2. This research could have implications for scientific publishing media in Indonesia.ABSTRAKJurnal ilmiah menjadi rujukan utama para akademisi. Tidak ada satupun di perguruan tinggi, khususnya perpustakaannya yang tidak memiliki koleksi jurnal ilmiah. Bacaan ilmiah semacam ini tentu ada yang mengorganisirnya. Penelitian deskriptif ini menggambarkan manajemen penerbitan Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi dan Kearsipan (KHJIPK). Dua yang ditekankan ialah proses penerbitan dan capaian prestasi. Data diperolah dari hasil wawancara dengan editor jurnal dan dokumentasi dari website jurnal. Hasil penelitian menunjukkan bahwa manajemen penerbitan dikelola secara daring dengan menggunakan aplikasi Open Journal System (OJS). Pada tahun 2017 KHJIPK terakreditasi Nasional peringkat Sinta 3, lalu pada tahun 2018 naik peringkat ke Sinta 2. Penelitian ini dapat berimplikasi pada media-media penerbit ilmiah di Indonesia.